SHAKH, S. (2010). LʹVIV – MISTO MOYEYI MOLODOSTY. TSISARSʹKO-KOROLIVSʹKA AKADEMICHNA HIMNAZIYA. LʹVIV: VYDAVNYTSTVO NATSIONALʹNOHO UNIVERSYTETU «LʹVIVSʹKA POLITEKHNIKA» (City: History, Culture, Society, 2019)
SHAKH, S. (2010). LʹVIV – MISTO MOYEYI MOLODOSTY. TSISARSʹKO-KOROLIVSʹKA AKADEMICHNA HIMNAZIYA. LʹVIV: VYDAVNYTSTVO NATSIONALʹNOHO UNIVERSYTETU «LʹVIVSʹKA POLITEKHNIKA». REVIEW